Implementasi Kebijakan ASN sebagai Pelaksana Kebijakan Publik dalam Meningkatkan Kinerja Pegawai pada Kantor Badan Kepegawaian Daerah, Provinsi Sumatera Utara - Anggraini, Heny; Zainuddin, Zainuddin; Hartono, Budi (Mahesa Research Center, 2022)
The objectives of this research are as follows: Knowing and analyzing the implementation of ASN Policy Functions as Implementing Public Policy in Improving Employee Performance at the Regional Civil Service Agency Office of North Sumatra Province. Knowing and explaining the supporting and inhibiting factors in the Implementation of ASN Policies Functioning as Implementers of Public Policies in Improving Employee Performance at the Regional Personnel Agency Office of North Sumatra Province. This research is a qualitative design. Research approach based on phenomenology and constructivism paradigm in developing science Thus, qualitative research based on phenomenology and constructivism paradigm becomes the basis for researchers to interpret research findings so that they become a description of the research that occurs. The policy implementation model developed by Edward III is called Direct and Indirect Impact on Implementation. According to Edward III, there are four variables or factors that influence public policy, namely Communication, Resources, Disposition and Bureaucratic Structure. The four factors must run simultaneously because the four factors are interrelated.